Gold-Catalyzed Dimeric Cyclization of Isoeugenol and Related 1-Phenylpropenes in Ionic Liquid: Environmentally Friendly and Stereoselective Synthesis of 1,2,3-Trisubstituted 2,3-Dihydro-1H-indenes - Morita, Nobuyoshi; Mashiko, Rie; Hakuta, Dai; Eguchi, Daisuke; Ban, Shintaro; Hashimoto, Yoshimitsu; Okamoto, Iwao; Tamura, Osamu (Synthesis, 2016)
Gold-catalyzed dimerization of isoeugenol and related 1-phenylpropenes in ionic liquid enabled environmentally friendly, stereoselective synthesis of 1,2,3-trisubstituted 2,3-dihydro-1H-indenes. Dimerization of isoeugenol or isohomogenol afforded diisoeugenol or diisohomogenol, respectively, with α-configuration, whereas dimerization of α-asarone furnished diasarone with γ-configuration.
Keywords: gold-catalyzed dimerization; ionic liquid; addition; cyclization; 1,2,3-trisubstituted 2,3-dihydro-1H-indenes